Snow White and Rose Red - Grimm, Jacob, 1785-1863.; Grimm, Wilhelm, 1786-1859.; Watts, Bernadette (New York : North-South Books, 1997)
A bear, befriended by two sisters during the winter, returns one day to reward them royally for their kindness.
First published in Switzerland under title Schneeweisschen und Rosenrot.
K-3
Keywords: Fairy tales; Folklore -- Germany; Fairy tales; Folklore -- Germany